ANALISA KEMATANGAN KARIR MAHASISWA PENDIDIKAN EKONOMI DITINJAU DARI STATUS SOSIAL EKONOMI KELUARGA - Tiya Ristin Rinanda; Muhammad Abdul Ghofur (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Career maturity in the world of teacher training today is an important capital in facing competition. Mapping the career maturity of educational science students is important to predict their chances of success as well as material for policy considerations related to learning. The population was 332 students with a sample of 180 students. This study uses a quantitative method with an analysis tool used, namely analysis of variance (ANOVA). The results obtained from this study state that there is no difference in career maturity of students with the socio-economic status of parents in the low, medium and high categories. However, the career maturity level of students with high socioeconomic status is generally lower if compared with the average value of low and medium socioeconomic status. The career maturity level of students with high socioeconomic status also varies greatly. Keywords: Career Maturity, Socio-Economic Status, Students